'Giving' and 'Making' in Early Runic Epigraphy1. (30th November 2012) - Mees, Bernard
Abstract: A survey of the early Germanic etymological semantics of 'giving' and 'making' is presented in light of the recent reaffirmation that early Nordic * taujan is etymologically related to Old Norse tœja 'grant, bestow, help, assist'. Contextualising the early runic fabricatory and dedicatory inscriptions in terms of sociological, textual and anthropological theory, a new interpretation of early runic pragmatics is developed. The new approach to early runic performance proferred seeks to explain the broader function (and context) of epigraphic production, not merely the most logical reading of individual texts. The early runic pragmatics of 'giving' and 'making' are employed as an analytical frame in which to analyse the socio‐cultural as well as linguistic meaning of a series of both functionally and textually related, often significantly stylised Iron Age epigraphs found on a range of early Scandinavian media: runestones, moor finds and migration‐era amulets.